Analisis Pertumbuhan Jumlah Kargo Terhadap Kegiatan Ekspor Impor Pasca Covid – 19 Pada Terminal Internasional PT. Indonesia Kendaraan Terminal Tbk. - Shania Amelia Dewi; Siti Sahara (Universitas 17 Agustus 1945 Semarang, 2024)
The aim of this research is to determine the flow of growth in export and import activities after Covid-19 and to determine the influence of the Covid-19 pandemic on the export and import activities of PT. Indonesia Vehicle Terminal Tbk. This research is descriptive qualitative research, research data obtained through data collection. After that, the data was analyzed qualitatively and then explained descriptively. Based on the research results, it was found that the flow of export growth in vehicle groups experienced increases and decreases at different times for each cargo, including CBU cargo, heavy equipment, and spare parts. Meanwhile, the flow of import growth for the vehicle group experienced a decline from 2019-2020 and experienced an increase again in 2021, this was due to restrictions related to the spread of the Covid-19 virus.